A germline exome analysis reveals harmful POT1 variants in multiple myeloma patients and families. Issue 4 (2nd September 2022) - Hakkarainen, Marja; Koski, Jessica R.; Heckman, Caroline A.; Anttila, Pekka; Silvennoinen, Raija; Lievonen, Juha; Kilpivaara, Outi; Wartiovaara‐Kautto, Ulla
Abstract: Observations of inherited susceptibility to multiple myeloma have led to active research in defining predisposing genes to the disease. Here, we analysed 128 plasma cell dyscrasia patients' germline whole‐exome sequencing data. Rare dominantly inherited pathogenic or likely pathogenic (P/LP) variant was found in 9.4% of the patients. Among the P/LP variants, CHEK2 ( p. Thr410MetfsTer15) was the most prevalent ( n = 5, 3.9%). Interestingly, P/LP variants in POT1 were identified in three patients (2.3%). Our findings broaden the spectrum of POT1 ‐related cancers and demonstrate the importance of the germline genetic analysis in hematological malignancies.